RECONSTRUCTING AND ASSESING VISUAL ARGUMENTS BASED ON FIGURATIVE ANALOGY - Kišiček, Gabrijela (Array, 2014)
Visual argumentation looks to remain an important topic for argumentation theory in the 21st century. Over the past decade, various scholars (Groarke, 1996, 2002 ; Birdsell & Groarke, 1996, 2007 ; Foss, 2005 ; Kjeldsen, 2000, 2012 ; Ripley, 2008 ; Slade, 2003 ; van den Hoven, 2012) have argued that visuals can be considered as logical arguments, and that major argumentative work can be accomplished through the use of visual images. This claim, however, has also been severely questioned by other authors (Blair, 1996 ; Fleming, 1996 ; Johnson, 2004) who recognize the power of visual images especially in a public discourse. But they by and large deny the possibility that they be arguments in their own right. Fleming (1996, p. 12) even suggests that “argumentation without the use of language is impossible.” There are several reasons for denying the existence of visual arguments, amongst them structural shortcomings such as a lack of syntactic arrangement and, generally, the lack of a linear production or interpretation process. Moreover, concerns have been raised pertaining to ambiguity and vagueness, but also include a confusion which could result when various interpretations of the same image are possible. Finally, methods to enable the assessment of an image’s argumentative value appeared to be missing. The objective of this paper is to discuss methods that make possible the reconstruction and assessment of specific visual arguments based on figurative analogies. What Govier (1987, p. 58) has called a priori analogies, “are arguments where similarities between entities belonging to entirely different spheres of reality are invoked” (Kienpointer, 2012, p. 111). Although authors such as Freely and Steinberg (2010) dismiss figurative analogies as logically insufficient, others view them as rational and relevant arguments which will nevertheless often lack strength (Perelman & Olbrechts-Tyteca, 1958 ; Mengel 1995 ; Woods 2004). We particularly question the argumentative strength of figurative analogies when these are based on visual images. To reconstruct and evaluate their plausibility and argumentative strength, we use a normative version for the reconstruction of verbal figurative analogies proposed by Kienpointer (2012), containing with five pragmatic parameters (i.e. “closeness” and “distance” of figurative analogy, burden of proof assigned to arguments, pro and contra arguments, “didactic” value and “seriousness” of figurative analogy). This allows us to draw a distinction between strong and weak arguments based on figurative analogy. Our main goal is to determine whether this method for the evaluation of verbal arguments can be applied, without further ado, also to visual arguments. Ten visual images of advertisements (e.g., “stop human trafficking”, “stop violence against women” etc.) that use figurative analogies will be presented, reconstructed and evaluated. Also applying the critical questions for the evaluation of arguments from analogy proposed by Walton (2008), we conclude that the distinction between strong and weak visual arguments is theoretically well determined, and also applicable without major difficulties to the material studied here.